VD_FINDINFO HC / 2012 / 136 vom 24. Februar 2012 - VD Tribunal cantonal (2012)
DÉCISION FINALE, DÉCISION PARTIELLE, DÉCISION INCIDENTE, DÉCISION D'IRRECEVABILITÉ | 129 al. 1 Cst-VD, 236 CPC (CH), 237 CPC (CH), 308 al. 1 let. a CPC (CH)